(untitled) (Homoeopathy for All, 2025)
In the realm of homeopathic pre scribing, efficacy is intricately tied to the purity and quality of both raw materials and the final remedies. A deviation from standards can signifi cantly impact therapeutic outcomes. Drug standardization, a cornerstone of homeopathy, involves a compre hensive evaluation encompassing pharmacognostical, physico-chem ical, and pharmacological param eters. This theoretical descriptive article delves into the intricacies of tests for qualitative and quantitative analysis in homeopathic drug stan dardization. By providing a theoreti cal framework, this article aims to deepen understanding of the phyto chemical screening tests utilized in drug standardization.